Four levels of meaningfulness of human life: from the perspective of the development model of togetherness (inspired by the works of O.S. Nikolskaya and F.E. Vasylyuk) - A.V. Novichkova (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Context and Relevance. We previously described a dynamic model of jointness, a general psychological unit for understanding the human being that integrates key insights from cultural-historical psychology. However, the model remains fairly abstract. Objective. In order for the model to be practically applicable, it is essential to showcase its capacity to comprehend the dynamic essence of human experience. Hypothesis. Psychological development proceeds through the emergence of the jointness domains within one's lifeworld: I, Thing, Goal, and You. These changes can be described using O.S. Nikolskaya's (2020) concept of affective organization of consciousness and behavior , while the inner work carried out can be understood through F.E. Vasilyuk's (2010) typology of coping with critical situations. Methods and materials. We compared two approaches to experiencing and, together with other psychological theories, used them to outline the ontology and phenomenology of four levels of jointness. We identified the psychological processes and types of fabric of meaning specific to each level. We drew a parallel with the evolution of living organisms and defined the biological values corresponding to each level. We also highlighted resonance and feedback as key biological mechanisms in the development of jointness. Results. Thus, we described models of four levels of jointness development and produced a detailed, multifaceted description of the four degrees of meaningfulness in human life. Conclusions. The proposed connection between the development of jointness, affective organization, and critical situations was broadly confirmed, with certain qualifications. The findings point to an evolutionarily continuous bio-psycho-socio-cultural organization of human existence and suggest the presence of a general anthropological trajectory of development.